2016
DOI: 10.1039/c6dt00120c
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of biogenic selenium nanoparticles in immunological and oxidative stress generated by enrofloxacin in broiler chicken

Abstract: Presently most bacteria are becoming antibiotic resistant. Due to this there is a deficiency of potent antibiotics, therefore we have to preserve and improve the efficiency of existing antibiotics by mitigating the side effects. Enrofloxacin (EFX) is an important antimicrobial used in veterinary practice but it is known to exert immune suppression antioxidant stress. In the present study, we report on: (a) the biosynthesis of selenium nanoparticles (Se NPs), and (b) their protective effect in reducing adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…3 One promising area of research is the application of nanotechnology towards selenium fabrication and use. [6][7][8][9][10] Nanoparticles (NPs) are particularly suitable as they possess high surface area to volume ratios, increased surface area, and increased interactions with biological targets, leading to higher availability and absorption by the host. [11][12][13] In addition, selenium NPs (SeNPs) possess lower toxicity than their elemental form; in mice, the LD 50 of selenomethionine was 25.6 mg Se/kg compared with 92.1 mg Se/kg for SeNPs.…”
Section: Introductionmentioning
confidence: 99%
“…3 One promising area of research is the application of nanotechnology towards selenium fabrication and use. [6][7][8][9][10] Nanoparticles (NPs) are particularly suitable as they possess high surface area to volume ratios, increased surface area, and increased interactions with biological targets, leading to higher availability and absorption by the host. [11][12][13] In addition, selenium NPs (SeNPs) possess lower toxicity than their elemental form; in mice, the LD 50 of selenomethionine was 25.6 mg Se/kg compared with 92.1 mg Se/kg for SeNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although organic selenium has a higher potential for uptake, there are some reports on more favorable performance of mineral selenium with vitamin E on the performance of poultry (Perez et al, 2010). While some researchers believe that applying mineral or organic selenium has no effect on the immune system of chickens (Biswas et al, 2006), numerous studies have shown that a new source called nano-selenium has a more favorable performance in poultry diets (Shirsat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, elemental Se particles produced by some bacterial strains have a very low bioavailability over extended periods of time 24 , 25 . BioSeNPs demonstrated antioxidant and anticancer activities in recent studies without mentioning its bioavailability in mice 5 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%